PENGARUH NAUNGAN DAN PUPUK FOSFOR TERHADAP PERTUMBUHAN DAN PRODUKSI NILAM (Pogostemon cablin Benth.) - Rosihan Rosman; Setyono Setyono; H Suhaeni (Pusat Penelitian dan Pengembangan Perkebunan, 2004)
The effect of shade and phosphor on the growth and production of PogostemonA pot experiment aiming at the optimal effect of shade and phosphor fertilizer on the growth and yield of Pogostemon plant of the Sidikalang type was carried out at Cimanggu experimental garden of Indonesian Spice and Medicinal Crops Research Institute, Bogor, from September 1998 to January 1999. The research was carried out factorially with a randomized block design with four replications. The treatments consisted of two factors, which are shade (without shade and 50% shade), and phosphor fertilizer (without phosphor, 0,69 g P/polybag, 1,38 g P/polybag). The result of the research showed that 50% shade treatment significantly increased the plant height, number of leaf, number of branch, wide of crown, stem diameter, fresh and dry leaf weight, fresh and dry stem weight. The P treatment (0,69 g P/polybag) significantly increased the number of branch, number of leaf and stem diameter. Significant on Interaction between shade and P Occuronly on stem diameter. The interaction of 50% shade with 0 g P/polybag showed the biggest dramecer treatment, followed by 50% shade with 1,38 g P/polybag and 50% shade with 0,69 g P/polybag